How to implement a successful smoking cessation intervention for adolescents?. (13th November 2019) - Vallata, A; Alla, F
Abstract: Background: Policies and programs implemented to promote smoking cessation among youth present disparate results. These variations are explained by interventions themselves but also by context, population and implementation characteristics. Our objective was to analyze these factors, related to enrollment and participation in a smoking cessation program, implemented in vocational or technical schools. Methods: Population factors were studied by a systematic review about determinants of smoking cessation among 10-24 years old, updating a previous one. Contextual and implementation factors were identified by a qualitative multiple cases study. A smoking cessation program, TABADO, had been implemented in 3 regions in France, in 10 vocational or technical schools (1 school/1 case). Data collection included 51 observations, 46 semi-structured interviews, and 3 interdisciplinary seminars. Results: The review identified 46 factors probably or possibly related to a successful smoking cessation, both individual (e.g. smoking frequency) and collective (e.g. relationship smoking status, anti-tobacco legislation). The case study allowed us to objectify positive or negative factors that influence the enrollment and the participation in the program (e.g. presence of a referent in the school, combination with the school program). Finally, we identified prerequisites to gather before starting such a program. Conclusions: This mixt design highlights factors on which we must focus to increase the success of a smoking cessation program for youth. A key factor is to tailor intervention and implementation modalities to the local context. Results enabled us to product a pragmatic guide, TABADO 2, which is now used in a national scaling process. They also will be used to build an intervention theory, which could be used for any smoking cessation intervention for youth. Acknowledgments: The TABADO IDF study group, Inca, the région Lorraine and the ARS Nouvelle-Aquitaine for their financial support. Key messages: A smoking cessation program must be a global strategy, considering contextual, population and organizational factors. Instead of trying to strictly apply a protocol, a complex intervention must be tailored to the context in which it is implemented.